2022
DOI: 10.3390/universe8080397
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in Galaxy Spin Directions—Analysis of Data from DES and Comparison to Four Other Sky Surveys

Abstract: The paper shows an analysis of the large-scale distribution of galaxy spin directions of 739,286 galaxies imaged by DES. The distribution of the spin directions of the galaxies exhibits a large-scale dipole axis. Comparison of the location of the dipole axis to a similar analysis with data from SDSS, Pan-STARRS, and DESI Legacy Survey shows that all sky surveys exhibit dipole axes within 52° or less from each other, well within 1σ error, while non-random distribution is unexpected, the findings are consistent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 266 publications
0
35
0
Order By: Relevance
“…As a model-driven method, it is not based on any kind of machine learning, and therefore it is not subjected to possible biases in the training data. The simple "mechanical" nature of Ganalyzer allows it to be fully symmetric (Shamir, 2021b(Shamir, , 2022c.…”
Section: Datamentioning
confidence: 99%
See 4 more Smart Citations
“…As a model-driven method, it is not based on any kind of machine learning, and therefore it is not subjected to possible biases in the training data. The simple "mechanical" nature of Ganalyzer allows it to be fully symmetric (Shamir, 2021b(Shamir, , 2022c.…”
Section: Datamentioning
confidence: 99%
“…Previous work using different telescopes showed that the spin directions of spiral galaxies form a statistically significant large-scale axis (Shamir, 2022b). That was done by fitting the spin directions to the cosine of the angle between the galaxies and every possible integer (α, δ) combination in the sky (Shamir, 2022c), as shown by Equation 1χ…”
Section: Identification Of a Possible Dipole Axis Alignmentmentioning
confidence: 99%
See 3 more Smart Citations